2019
DOI: 10.3390/ijms20061405
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 Ligand Expression in Epithelial Thyroid Cancers: Potential Clinical Implications

Abstract: The new immunotherapy targeting the programmed cell death 1 (PD-1) receptor and its cognate ligand PD-L1 has renewed hopes of eradicating the most difficult human cancers to treat. Among these, there are the poorly differentiated and anaplastic thyroid cancers, unresponsive to all the therapies currently in use. In the present review we will summarize information regarding the expression of PD-L1 in the different thyroid cancer histotypes, its correlation with clinicopathological features, and its potential pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 95 publications
(189 reference statements)
2
54
0
Order By: Relevance
“…As reported in other publications, we explored the possibility of a link between PD-L1 and BRAF V600E. 45,46,48,[58][59][60][61] Angell et al observed that BRAF V600E mutation was associated with immunosuppressive mechanisms in PTC, including PD-L1 expression. 45 According to published reports, the rate of PD-L1 expression is qualitatively and quantitatively higher in BRAF V600E-mutated thyroid lesions, even up to 53% in 1 study.…”
Section: Cancer Cytopathology March 2020mentioning
confidence: 86%
“…As reported in other publications, we explored the possibility of a link between PD-L1 and BRAF V600E. 45,46,48,[58][59][60][61] Angell et al observed that BRAF V600E mutation was associated with immunosuppressive mechanisms in PTC, including PD-L1 expression. 45 According to published reports, the rate of PD-L1 expression is qualitatively and quantitatively higher in BRAF V600E-mutated thyroid lesions, even up to 53% in 1 study.…”
Section: Cancer Cytopathology March 2020mentioning
confidence: 86%
“…The limited retrospective data available to date suggest that PD-L1 could represent a prognostic marker for patients with thyroid cancer 17 and that anti-PD-1/PD-L1 therapies could be an option for a very limited subset of patients who have aggressive thyroid cancers (PDTC or ATC) that are resistant to the currently available therapies. 1,[6][7][8]21 Provided cytologic samples are deemed adequate for PD-L1 testing, whether the information provided by this test will be clinically useful preoperatively is doubtful, and many issues remain to be addressed. It is also likely that a single test such as PD-L1 immunohistochemistry cannot be used as a reliable surrogate to predict the efficiency of immunotherapy and that taking into account other important components that affect complex and dynamic tumor-immune interactions will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic inflammation is a well known risk factor for tumor initiation and promotion, the ability of cancer cells to avoid the immune damage by disabling components of the host immune system is now considered a hallmark of cancer. In cancer, the immune response is turned off by various mechanisms, including: 1) inactivation of cytotoxic T lymphocytes and natural killer cells by secreting immunosuppressive factors; 2) recruitment of immunosuppressive cells (eg, myeloid‐derived suppressor cells, regulatory T cells); and 3) expression of inhibitory ligands for the immune checkpoint receptors, including CTLA‐4 (cytotoxic T‐lymphocyte associated protein 4) and PD‐L1 (programmed death‐ligand 1) . Therefore, the complex interactions between immune cells and tumor cells play a major role in tumor development, including tumor growth, invasion, and metastasis, and subsequent patient outcomes .…”
Section: Pd‐l1 Expression and Thyroid Cancer Diagnosismentioning
confidence: 99%
See 2 more Smart Citations